On bending strength of superhard composite materials based on WC–Co hardmetals - Golovchan, V. T. (Strength of materials, 2009)
We present analytical algorithms for computing the ultimate bending strength of superhard composite materials based on WC–Co hardmetals. The study is performed for fine-grained materials (where mean particle size of the dispersed superhard phase d C and that of carbide grains d WC are of the same order of magnitude) and coarse-grained materials (with d C ≫ d WC ). The strength of the composite is assumed to be governed by the strength of its hardmetal matrix. The stressed state of the matrix is assessed through volume-average microstresses for fine-grained materials and interface-average stresses for coarse-grained composites. The calculated results presented in the form of tables and graphs have been analyzed. The strength has been found to decrease drastically with increasing particle size of the superhard phase and its concentration in the composite.